Effects of the COVID-19 pandemic on maternal and perinatal outcomes: A cross-sectional study in Peru 2020-2021 vs 2019 - Huanco-Apaza, Diana (2023)
Introduction: Confinement, fear of hospitalization during pregnancy, and uncertainty about delivery care during the COVID-19 pandemic, can affect perinatal maternal health outcomes.Objective: To assess the effects of the COVID-19 pandemic on maternal and perinatal outcomes in Peru during the pandemic period compared to the pre-pandemic period.Materials and Methods: Cross-sectional analytical study, with a before-and-after approach, based on live birth certificate (CNV) data, including all live births in Peru with CNV; 2020 and 2021 (pandemic) were compared to 2019 (pre-pandemic). Adolescent pregnancy rate, cesarean section rate, place of birth, type of health service, premature delivery and low birth weight were evaluated. Chi2 was used to compare proportions using Stata V.17. Information was requested from the Ministry of Health, respecting confidentiality.Results: The overall adolescent pregnancy rate decreased from 11% (pre-pandemic) to 10.5% and 10.7% (pandemic); while those under 14 years of age decreased significantly from 0.27% in 2019 to 0.25% in 2020 and increased to 0.31% in 2021. The use of the maternity service in private institutions increased significantly from 8.9% to 12.1% and 12.5% (pandemic), as well as home delivery from 0.8% (pre-pandemic) to 1.3% and 2.1% (p<0.01). Preterm birth was 6.8% in 2019, decreased to 6.4% in 2020 and returns to 6.9% in 2021. The percentage of low weight from 6.2% in pre-pandemic, decreased to 6.0% in 2020, rising to 6.4% in 2021. The caesarean section rate remains between 38% and 39%.Conclusions: Our findings suggest an increase in pregnancy in children under 14 years of age, use of private services and home delivery; but reduction in premature births and low birth weight in the first year of the pandemic and return in the second year.